A visualize simulator for nodes mobility in manets - Toh, Hong Yi. (2010)
A Mobile Ad Hoc Network (MANET) is a collection of wireless devices forming a self-configuring network without using any communication infrastructure. Random waypoint mobility is a popular model used in simulation of MANET communication protocol. Hence, a visualized simulator would be developed to simulate nodes mobility within a MANET using the random waypoint mobility model. A new feature, re-active mobility is added to further enhance the random waypoint mobility model. In this report, the inter-arrival time of nodes movements using the random waypoint mobility model is studied. We would analytically derive the inter-arrival using the geometric probability and simulations is carried out to verify the estimation accuracy of the results obtained by the simulator.